2021
DOI: 10.3390/app11062886
|View full text |Cite
|
Sign up to set email alerts
|

Spondias mombin Seed Oil Compounds Identification by Raman Spectroscopy and NMR

Abstract: Spondias mombin L. has been used in traditional medicine to treat some cases such as infections and inflammations. Some researchers have reported that its biological components, such as carotenoids, carotenes, and phenols, have been characterized primarily by HPLC analysis. Here, we report on the characterization of Spondias mombin L. seed oil by Raman spectroscopy, and the profile identification of fatty acids by 1H-NMR and 13C-NMR spectroscopy. The oil was extracted from different weight volumes of seeds usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…López‐Camacho et al. (2021) evaluated the yellow mombin seed oil describing a concentration‐dependent antioxidant activity, with a maximum ABTS radical inhibition of 45%. Another study with Brazil plum residues showed similar elimination of ABTS and DPPH to that reported in the present study (Xavier et al., 2022).…”
Section: Resultsmentioning
confidence: 99%
“…López‐Camacho et al. (2021) evaluated the yellow mombin seed oil describing a concentration‐dependent antioxidant activity, with a maximum ABTS radical inhibition of 45%. Another study with Brazil plum residues showed similar elimination of ABTS and DPPH to that reported in the present study (Xavier et al., 2022).…”
Section: Resultsmentioning
confidence: 99%
“…While both walnut and bluebell oil samples showed a higher percentage of unsaturated fatty acids than Gd cottonseed, walnut was dominated by PUFAs, and bluebell was dominated by MUFAs. Similarly, Barison et al [ 60 ] applied these 1 H NMR spectral characteristics to develop a simple method for the determination of linolenic, linoleic, oleic, and saturated fatty acids. They found the ratio changes of these fatty acid compositions in oil samples of rice, sunflower, corn, canola, olive, and soybean.…”
Section: Resultsmentioning
confidence: 99%
“…They found the ratio changes of these fatty acid compositions in oil samples of rice, sunflower, corn, canola, olive, and soybean. However, it is impossible to quantitatively compare those data with those in Table 2 not only due to the difference in the specific fatty types but also as no tabulated quantitative values were presented in [60]. a : Averages calculated per the five-year data in [59].…”
Section: H Nmr Spectral Features Of Nonpolar Oil Fractionmentioning
confidence: 99%
“…Essential oils from citrus fruits are a group of natural flavors and fragrances which are popularly used in the food and pharmaceutical industries, daily chemical products, and in the health care field [8][9][10][11][12]. The products of medicinal plants like EOs and their antimicrobial properties have been empirically recognized for centuries, but recently the antimicrobial properties have been studied and confirmed scientifically [13][14][15]. These EOs effectively control the growth of different microorganisms like fungus, yeasts, bacteria, etc., which has been reported in several studies [16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%